Alström syndrome caused by deletion in ALMS1 gene fixed in a Northern Pakistan recurrent haplotype (Indian Journal of Case Reports, 2017)
Reduced genetic variability in isolated populations promotes the prevalence of long contiguous stretches of homozygosity (LCSH) that may carry deleterious mutations, manifesting recessive syndromes such as Alström syndrome (OMIM # 203800), caused principally by mutations in exons 8, 10, and 16 and deletions/insertions along the ALMS1 gene. Here, Sanger sequencing of these exons and whole-genome copy-number variants/single-nucleotide polymorphisms (SNPs) microarray were used to characterize ALMS1 gene in a 19-year-old Pakistani female with Alström syndrome. Sequencing did not reveal pathogenic alterations but described a set of homozygous polymorphisms. The microarray revealed these SNPs were included in an 8.24 Mb LCSH in 2p12.2p13 that contained a homozygous deletion including exons 13-16 of ALMS1 gene. Therefore, reduced genetic variability in Pakistani population enhanced the inheritance of the homozygous deletion causing Alström syndrome. The comparison of the deletion with known deletions spanning exons 13-16, described on Middle Eastern patients, suggested a fixation of the deletion in a specific haplotype.